Christians and Jews in the Ottoman Arab world : - Masters, Bruce Alan (Cambridge University Press, 2001)
Masters explores the history of Christians and Jews in the Ottoman Empire and how their identities evolved over four hundred years. While early communities lived within the hierarchy of Muslim law, the nineteenth century witnessed radical change. In response to Western influences, conflict erupted between Muslims and Christians across the empire. This marked the beginning of tensions that informed the rhetoric of religious fundamentalism in the empire's successor states throughout the twentieth century. Thus Masters negotiates the present through the past, contributing to our understanding of the contemporary Muslim world